Ten Years from the Appeal of Blois. An Appeal for a Debate - Skórzyńska, Izabela (Sensus Historiae, 2019)
Ten years after the Appeal from Blois, almost everything has changed in the Polish public sphere. The democratization of history and its policies took on new forms and were enriched with new, often controversial, contents. In addition to the existing ones, new social actors and new institutions and the media, for which history has become as much a subject of research and knowledge as also a weapon in an ideological struggle, have appeared. This turn is well visible in the so-called memory rights, whose status, content and effects bring opportunities, but also threats to the freedom of science and civil liberties.At the same time, the debate about the past, intercepted by the populists, has entered a phase of the sometimes sharp conflict over history and memory as a keystone for national and civic identity. In these circumstances, particularly a return to the public debate about the recent past, is not only cognitively invigorating, but also ethically expected.